Differences in clinical outcomes between octogenarian and nonagenarian patients with acute heart failure. Issue 3 (9th February 2023) - Sakaguchi, Kunihiko; Uemura, Yusuke; Shibata, Rei; Ishikawa, Shinji; Takemoto, Kenji; Murohara, Toyoaki; Watarai, Masato
Abstract : Aim: The number of hospitalized super‐elderly patients with heart failure (HF) has increased with aging of the population. These patients are associated with poor clinical outcomes with the advance of age; however, few reports regarding acute HF have compared the clinical outcomes of nonagenarians with those of octogenarians. Methods: This study enrolled 683 patients aged ≥80 years who were admitted to our institution for acute HF between 2016 and 2020. The outcomes of interest were the 1‐year all‐cause mortality, incidence of cardiac events (cardiac‐related death or HF‐related readmission), and physical function during hospitalization of patients with survival‐to‐discharge. Physical function was evaluated using the Barthel index. Results: Post‐discharge all‐cause mortality, particularly non‐cardiac mortality, was significantly higher in nonagenarians than octogenarians. Conversely, the incidence of cardiac death or rehospitalization for HF after discharge was comparable between the two groups. On admission, the Barthel index score was significantly lower in nonagenarians than octogenarians, and further decreased during hospitalization. Nonagenarians required social support at discharge more often than octogenarians (67.4% vs. 44.4%; P < 0.001). Conclusions: The current study demonstrated that nonagenarians have poorer non‐cardiac outcomes and were more vulnerable regarding physical activities than octogenarians among patients with acute HF. Holistic medical care, including palliative care and social support, will be increasingly required with increasing age. Geriatr Gerontol Int 2023; 23: 227–233 . Abstract : Physical function vulnerability, the need for adjustment of the post‐discharge life according to the patient's condition, and the increase in non‐cardiac events are the major challenges in managing acute heart failure in nonagenarians compared with octogenarians.